Green Waqf for Rural Empowerment: : Integrating Cash Waqf, Biomass Energy, and Sustainable Development - Dede Rukanda; Sofyan Halim (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
This study introduces a novel, empirically-grounded framework—the Cash Waqf Linked Biomass Energy (CWLBE) model—that demonstrates for the first time a viable pathway for integrating Islamic social finance with a circular bio-economy to achieve sustainable rural development. Amidst the global push for renewable energy, this research addresses the critical gap between the vast potential of waqf and its practical application in community-based energy projects. Employing a seven-stage Research & Development (R&D) methodology in a pilot project in West Java, Indonesia, this study designed and validated a multi-stakeholder ecosystem that is Sharia-compliant, economically sustainable, and operationally replicable. The model successfully integrates public and corporate waqf to fund the cultivation of high-yield Calliandra calothyrsus biomass, creating a closed-loop value chain managed by the local community. Key findings from the pilot reveal significant social and economic impacts, including the creation of new income streams for rural farmers and the generation of a social surplus for community development, alongside strong market acceptance from both digital-native donors and ESG-focused corporations. The CWLBE model offers a scalable blueprint for policymakers and practitioners to leverage Islamic philanthropy as a strategic instrument for simultaneously advancing energy independence, economic empowerment, and climate action, contributing directly to the Sustainable Development Goals (SDGs).